The role of celebrity images on disordered eating behaviours and body dissatisfaction among female adolescents in Malaysia - Lisa Marie Ann, Ambrosc; Rashini Thevi Nach, Nacathiran; Vanessa Nicole, Stephen Dass (2019)
This study aims to identify the effect of celebrity images on disordered eating behaviours with body dissatisfaction being the covariate variable among female adolescents in Malaysia. A 2 × 3 between subjects, pretest-posttest design with semi experimental approach was used together with a purposive sampling method for the purpose of participants’ recruitment. The target participants of this study are female adolescents between the ages of 14 and 19 years old. A total of 146 participants represent the sample of this study. The responses of the participants are obtained via questionnaires with them filling up their demographic information, the Eating Attitude Scale (EAT-26) for disordered eating behaviours and the Body Dissatisfaction Scale to analyse body dissatisfaction. Celebrity images (treatment group) and coke bottle images (control group) were categorized into two categories mainly thin/normal and plus size. Descriptive test, ANOVA, Linear Regression, and ANCOVA tests were utilized to analyse the data obtained. Through the analysis, this study is able to identify that there is no significant difference in terms of disordered eating behaviours between celebrity images when body dissatisfaction is controlled. This study also identifies that there is a significant difference between celebrity images, control images and body dissatisfaction especially among plus sized individuals. There was no significant difference found between celebrity images, control images and disordered eating behaviours. No statistically significant relationship was also identified between body dissatisfaction and disordered eating behaviours. Finally, there was no statistically significant difference between the BMI of the participants and the subscales of EAT-26.